Digital Global Business Services: A diversification prospect for South African telecoms operators owning submarine cables - Ntseuoa, Pontso (University of the Witswatersrand, Johannesburg, 2023)
With the advent of the Fourth Industrial Revolution and digital transformation, telecommunications operators core business has become gradually commoditised with most of their revenues being cannibalised by “edge-players” who render innovative digital services, piggyback on telecoms operators’ connectivity infrastructure, whilst easily bypassing them to reach the industry’s lucrative client base. This poses a problem as the diminishing revenues of the telecoms operators mean they may not be sustainable in the future and might eventually collapse. This qualitative research explored a potential business case for South African telecoms operators owning submarine cables on how they can possibly diversify into digital Global Business Services (GBS), servicing new international markets, in a quest to expand their revenue generation prospects. Convenient sampling method was employed with the initial data collection, then followed by purposive and snowballing sampling approaches to reach 10 interview participants who are executives in the GBS and telecoms industries. Data was collected using semi-structured in-depth interviews and analysed using theoretical thematic analysis, based on 4 predetermined themes of vendor configurations and strategies, prerequisite strategic resources, prerequisite capabilities, and prerequisite core competencies premised by the study’s conceptual framework. The study found that SA telecoms operators with ownership in submarine cables, do have the potential to successfully diversify into the digital GBS industry servicing new international markets. The study determined that entering the digital GBS industry requires comprehensive market research, understanding of target markets and countries, collaborations, investment in talent, and leveraging of unique assets. The study also recommended that SA telcos should focus on their existing strengths and adapt to evolving digital technologies and global work environments in order to successfully enter into this competitive digital Global Business Services industry
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business
Keywords: 4IR Technologies; Global Business Service; Offshoring; Outsourcing; Resource Based View Theory; UCTD; SDG-9: Industry, innovation and infrastructure